FORMATION OF PHYSICAL EDUCATION OF THE PERSON ON THE BASIS OF THE COMPETENCE APPROACH - Aleksandr Kudrya; Dmitry Gladkikh; Anastas Dzhavakhov (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the availability of the necessary occupation for the body of knowledge, skills and related specific intellectual and creative abilities, as well as personal qualities, are extrapolated to work through a certain set of competencies or a particular expertise. The basic components ofprofessional competence in the context of physical culture and pedagogical science.